To Sell an Unconventional Product, Tell a Compelling Story. Harvard Business Review, - Cutolo, Donato; Ferriani, Simone (Harvard Business, 2023)
Imagine you are an entrepreneur who loves to challenge the status quo. You’ve just come up with a unique product you’re excited to share with the world, but you’re also worried that people won’t understand it. What should you do?
Keywords: 53 Ciencias Económicas::5311 Organización y dirección de empresas; ODS 9 - Industria, innovación e infraestructura; ODS 8 - Trabajo decente y crecimiento económico; ODS 4 - Educación de calidad